Development of solid oxide fuel/electrolyser cell stack - Wijaya, Virvandy (2015)
Solid oxide cell (SOC) which comprises solid oxide fuel cell (SOFC) and solid oxide electrolyser cell (SOEC) is an emerging technology for electricity generation due to its high conversion efficiency and low environmental hazards. Nevertheless, the application of SOFC unit cell is hindered by its low voltage and peak power density. This study focuses on the design and development of planar type SOFC stack structure which can produce higher output power to meet the application requirement. Large-area fuel electrode-supported samples were initially prepared using aqueous-based tape casting method in conjunction with co-sintering process, particularly for the fabrication of YSZ electrolyte and NiO-YSZ fuel electrode layer. The printing method was also employed to manufacture the LSCF-CGO air electrode layer as well as current collecting layer on both cathode and anode substrates. Prior to stack setup, button cell performance evaluation was conducted in both fuel cell and electrolyser mode, which revealed a maximum power density of 449 mW/cm2 at 800oC, suggesting that an ideal performance of the sample had been obtained. Microstructure characterisation using scanning electron microscope (SEM) also showed that good sample microstructure had been achieved, with dense electrolyte and porous electrode layer. Single cell stack structure with cross-flow type structure and internal gas manifold was then assembled by using several additional components such as stainless-steel based interconnecting plates, mica sealing gasket, platinum mesh and porous nickel foam. Current-voltage characteristic of the stack indicated that higher hydrogen flow rate supplied and higher loaded mechanical pressure resulted in the increase in stack performance. In addition, a peak power density of 65.9 mW/cm2, power output of 5.1 W and open circuit voltage of 0.919 V were generated when the single cell stack with 10 cm x 10 cm unit cell (effective area 77.44 cm2) was operated at 800oC with 1.5 L/min of humidified H2 as fuel and 4 L/min of air as oxidant. The SOFC stack structure was successfully developed and tested in this study. Nonetheless, further work is required to enhance the performance of the stack and to scale up the experiment by incorporating more unit cells to the stack structure.